Public awareness of forensic odontology and willingness to enroll in a prospective dental registry: A survey conducted in Saudi Arabia - Mahmoud Salam; Nedal Al-Rawashdeh; Adel F. Almutairi (Elsevier, 2020)
Background: The establishment of a national dental registry provides a great opportunity for the healthcare and criminal investigation systems. Its feasibility would rely mainly upon public knowledge and a willingness to contribute dental profiles. The aim of this study was to evaluate the level of awareness among the Saudi public of forensic odontology and to evaluate their willingness to participate in a prospective national dental registry. Methods: A cross-sectional survey based on a self-administered survey questionnaire was conducted in 2018 at the Al-Janadriyah National Festival in Riyadh, Saudi Arabia. Visitors were questioned about their demographic data and responded to 20 knowledge statements using the alternatives "correct", "incorrect", or "don't know". Their perception towards registries was assessed using 15 statements and a 5-point Likert scale. The percentage mean score (PMS) of knowledge, the mean positive response rate (MPRR) of participant perception, and their willingness to participate in a prospective dental registry were assessed with respect to their demographic characteristics. Results: Complete surveys were received from 812 study participants (85.5% response rate). The PMS ± standard deviation of knowledge was 39.8 ± 22.5 and the MPRR of perception was 64.7 ± 25.5. More than two-thirds of the responders (n = 548, 67.5%) indicated a willingness to register in a future national dental registry. Differences in knowledge were identified with regard to sex, marital status, education, and occupation, while differences in perception and willingness to enroll were influenced by sex. After adjustment for possible confounders, female participants and employed participants were 1.7 times (95% confidence interval [CI] = 1.2-2.4) and 1.6 times [95% CI = 1.1-2.5] more likely to enroll in the proposed registry (P = 0.004 and P = 0.03, respectively). Higher knowledge and perception scores were associated with more willingness to enroll in the national dental registry (adjusted [adj.] P = 0.03 and adj. P < 0.001, respectively). Conclusions: A future national dental registry in Saudi Arabia is expected to be well-received by the public. An improvement in the public's knowledge regarding the importance of forensic dentistry is expected to encourage their active enrollment in such a registry. Although women and employed participants were more willing to enroll, it is too early to predict the rates of participation, given the fact that nationwide marketing surveys have yet to be launched. Keywords: Perception, Knowledge, National, Dental, Registry, Forensic, Saudi